Cabaran dan peluang graduan baharu era teknologi moden - Shamsudin, Mohd Zubairy (Faculty of Health Sciences, Universiti Selangor, 2025)
The rapid advancement of digital technologies and the emergence of Industry 4.0 have significantly transformed the employment landscape for new graduates. Modern workplaces are increasingly shaped by artificial intelligence, automation, and digitalisation, requiring graduates to be more flexible, skilled, and future-ready than ever before. This topic explores how these technological shifts are reshaping career expectations and the realities faced by fresh graduates entering the workforce.